2001
DOI: 10.1007/s004360000332
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a proteasome α-chain from Giardia lamblia

Abstract: To begin to characterize the components of the 20S proteasome of Giardia lamblia, we have cloned a genomic sequence encoding an alpha-chain (type alpha3/C9, predicted size 244 amino acid residues). Southern analysis indicated that a single gene codes for this protein, and a Northern blot exhibited a single signal at 850 nt. An antiserum against a C-terminal fragment of the alpha-chain expressed in Escherichia coli reacted with a single protein band of Mr 27,000 that was present at constant levels in trophozoit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
(15 reference statements)
2
2
0
Order By: Relevance
“…Western blotting of protein extracts corresponding to these time points also indicated that there was no detectable change in the levels of the protein (Figure 6 b). This observation is consistent with the lack of change in the expression of the CP subunits during encystation [ 35 ]. Thus, based on analyses of the gene expression and protein levels in trophozoites and encysting trophozoites, it may be concluded that the decreased localization of GlRpn10 at the flagellar pore regions during encystation is likely to involve redistribution of the protein from these locations, rather than decreased gene expression or protein degradation.…”
Section: Resultssupporting
confidence: 89%
“…Western blotting of protein extracts corresponding to these time points also indicated that there was no detectable change in the levels of the protein (Figure 6 b). This observation is consistent with the lack of change in the expression of the CP subunits during encystation [ 35 ]. Thus, based on analyses of the gene expression and protein levels in trophozoites and encysting trophozoites, it may be concluded that the decreased localization of GlRpn10 at the flagellar pore regions during encystation is likely to involve redistribution of the protein from these locations, rather than decreased gene expression or protein degradation.…”
Section: Resultssupporting
confidence: 89%
“…Confocal microscopy analysis demonstrated that the giardial 20S core complex and 19S cap structure were associated with ESV membranes during early encystation until at least 7 h after induction. As noted previously, the expression of proteasome subunits is not upregulated in encysting cells [ 47 ]. The confocal microscopy data indicated a relocalization from more peripheral sites in the cytoplasm to the vicinity of ESVs, indicating a high rate of retrotranslocation of organelle proteins destined for degradation.…”
Section: The Role Of Proteasomes In Parasite Biology and Virulencesupporting
confidence: 52%
“…A study of the seven genes that encode the α subunits of the G. duodenalis proteasome indicated that the α -proteasome gene family evolved quickly from a single gene in the Archaea to seven or more genes in Eukarya [ 46 ]. The G. duodenalis 20S proteasome appears to be similar to that described in eukaryotic cells, containing a divergent set of α subunits [ 47 ]. Proteomics approaches performed to discover novel proteins associated with the stage-specific, Golgi-like encystation-specific vesicles (ESV) identified cytoplasmic and luminal factors of the endoplasmic reticulum quality-control system, that is, several structural ( α ) and catalytic ( β ) proteasome subunits.…”
Section: The Role Of Proteasomes In Parasite Biology and Virulencementioning
confidence: 99%
“…Thus it is not unlikely that this protein would be associated with S/MARs and have DNA binding properties. There have been reports on the proteasome 20 S of Giardia lamblia [47,48], where Emmerlich et al showed the 14 subunits making up this proteasome structure. Though the annotated genome of Giardia shows the presence of several of the proteasome 26 S subunits, no detailed analysis has been done on these proteins in Giardia .…”
Section: Discussionmentioning
confidence: 99%